How the European Union legislations are tackling the burden of diabetes mellitus: A legal surveillance study - Nour Mahrouseh; Nour Mahrouseh; Szabolcs Lovas; Diana Wangeshi Njuguna; Diana Wangeshi Njuguna; Noel Johny Nellamkuzhi; Carlos Alexandre Soares Andrade; Carlos Alexandre Soares Andrade; Wilhelmina Egyirba Sackey; Anggi Septia Irawan; Anggi Septia Irawan; Orsolya Varga; et al. (Frontiers in Public Health, 2022)
IntroductionSurveillance of the European Union's (EU) legislations on the prevention of diabetes mellitus (DM) is needed, to more effectively tackle the rising prevalence of DM.MethodsThis legal surveillance was carried out through a systematic search and screening, using EUR-Lex database to identify treaties, acts, and other legal documents for prevention of DM, non-communicable diseases (NCDs) and obesity, followed by their content analysis and assessment according to DM specific guidelines, target population and functional categories.Results and discussionWe found 22 legislations aimed at preventing DM, NCDs and obesity, but only 5 out of them specifically addressed preventing DM. The aims of legislations covered a broad spectrum of themes indicated by DM specific guidelines, mostly initiatives of life-course approach in preventing DM, NCDs and obesity from the area of energy intake. The target group of most legislations was the general population; high-risk subgroups such as pregnant women were hardly ever the primary target group. Our results prove that the EU has made cross-sectoral legislative efforts to reduce the disease burden and prevent DM but does not exhaust all possibilities. However, given its persistently rising DM prevalence, it is imperative to make sure that DM is a top health priority for various EU authorities and is incorporated into new initiatives, policies and laws.